Analysis of Students’ Concept Understanding in Redox Materials and Compound Nomenclature After Application of the Blended-Problem Based Learning Method - Musyarofah, Musyarofah; Susilaningsih, Endang; Susilogati Sumarti, Sri (Universitas Negeri Semarang, 2020)
Understanding the concept is a very important factor to achieve maximum learning goals. In the learning process required a learning method that is applied by a teacher so that students easily understand the concept. This study aims to determine the understanding of the concept of class X students on redox material and compound nomenclature after the application of the Blended-Problem Based Learning method. This type of research is a case study that uses a combination of qualitative and quantitative methods involving 36 high school class ten students from the 2018-2019 academic year. The sampling technique is done by purposive sampling. Understanding students' concepts using reasoned questions, that are three layers of multiple choice tests. The results of the analysis of students' understanding of concepts on redox material and compound nomenclature after the application of the Blended-Problem Based Learning method showed that of 27 of 36 students (75%) understood the concept of redox and compound nomenclature, 8 out of 36 students (22%) misconceptions, and 1 of 50 students (0.3%) did not understand the concept of redox and compound nomenclature. Application of the Blended-Problem Based Learning model can help students to understand the redox reaction material and compound nomenclature.